NME3 binds to phosphatidic acid and mediates PLD6-induced mitochondrial tethering - Su, You-An; Chiu, Hsin-Yi; Chang, Yu-Chen; Sung, Chieh-Ju; Chen, Chih-Wei; Tei, Reika; Huang, Xuang-Rong; Hsu, Shao-Chun; Lin, Shan-Shan; Wang, Hsien-Chu; Lin, Yu-Chun; Hsu, Jui-Cheng; et al. (The journal of cell biology, 2023)
Mitochondria are dynamic organelles regulated by fission and fusion processes. The fusion of membranes requires elaborative coordination of proteins and lipids and is particularly crucial for the function and quality control of mitochondria. Phosphatidic acid (PA) on the mitochondrial outer membrane generated by PLD6 facilitates the fusion of mitochondria. However, how PA promotes mitochondrial fusion remains unclear. Here, we show that a mitochondrial outer membrane protein, NME3, is required for PLD6-induced mitochondrial tethering or clustering. NME3 is enriched at the contact interface of two closely positioned mitochondria depending on PLD6, and NME3 binds directly to PA-exposed lipid packing defects via its N-terminal amphipathic helix. The PA binding function and hexamerization confer NME3 mitochondrial tethering activity. Importantly, nutrient starvation enhances the enrichment efficiency of NME3 at the mitochondrial contact interface, and the tethering ability of NME3 contributes to fusion efficiency. Together, our findings demonstrate NME3 as a tethering protein promoting selective fusion between PLD6-remodeled mitochondria for quality control.
Online veröffentlicht: 16. August 2023
Gesehen am 04.12.2023